Evaluation of energy expenditure when wearing Hoka running shoes - Loy, Kelsey A. (My University, 2015)
The purpose of this study was to detetmine ifHOKA shoes positively or negatively affect oxygen consumption while running. Subjects included 16 proficient ru1mers (8 males and 8 females), between 20-65 years of age. All subjects ran 3, 6-minute bouts at a self- selected pace. Each subject ran in HOKA shoes, standard New Balance running shoes, and New Balance shoes with a weight added to match that of the HOKA's mass. Subjects were allowed a 4-minute break to recover and change shoes between bouts. No significant differences were observed in V02, HR, or energy expenditure between the three shoe conditions. Additionally, RPE remained unchanged. Despite their new design aspects, HOKA shoes do not seem to significantly affect running economy.
Keywords: Shoes; Running; Energy expenditure